2023
DOI: 10.3390/d15040512
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians of Rwanda: Diversity, Community Features, and Conservation Status

Abstract: The diversity and distribution of the amphibians in Rwanda was critically reviewed to provide a reliable species inventory for informed conservation management. The checklist of the amphibian species of Rwanda is based on results of our own fieldwork, historical records compiled from the literature, and examination of voucher specimens in museum collections. A total of 62 species are recorded, and 22 further species listed in field guides and open-access data bases are discussed, identified as erroneous record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 81 publications
(299 reference statements)
1
10
0
Order By: Relevance
“…Rwanda is positioned in Central Africa, immediately south of the equator between latitude 1• 4′ and 2• 51′ S and longitude 28• 63′ and 30• 54′ E. According to the 2012 Fourth Rwanda Population and Housing Census, the country is subdivided into four (Northern, Southern, Eastern, and Western) geographically situated provinces plus Kigali town (the capital, in the center). These provinces break up into thirty (30) districts, the most essential administrative regions of Rwanda's decentralization system, sectors (416), cells (2148), and villages (14,837), which cowl a 26,338 km2 location that houses 10,515,973 inhabitants (Dehling and Sinsch, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Rwanda is positioned in Central Africa, immediately south of the equator between latitude 1• 4′ and 2• 51′ S and longitude 28• 63′ and 30• 54′ E. According to the 2012 Fourth Rwanda Population and Housing Census, the country is subdivided into four (Northern, Southern, Eastern, and Western) geographically situated provinces plus Kigali town (the capital, in the center). These provinces break up into thirty (30) districts, the most essential administrative regions of Rwanda's decentralization system, sectors (416), cells (2148), and villages (14,837), which cowl a 26,338 km2 location that houses 10,515,973 inhabitants (Dehling and Sinsch, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetic analyses have repeatedly demonstrated that small-sized Arthroleptis species considered to belong to Schoutedenella do not form a distinct clade separated from larger species and Schoutedenella is now widely recognized as a junior synonym of Arthroleptis [6,12]. A number of small Arthroleptis species have been described from the mountains and the graben valley of the Albertine Rift [3,8,[13][14][15][16], and three species of Arthroleptis have been recorded from Rwanda [17]. Arthroleptis adolfifriederici Nieden, 1911 was described from the "Bugoiewald" and the "Rugegewald" (nowadays Gishwati and Nyungwe Forest, respectively) in Rwanda and is easily identified by its large size, smooth dorsum and long and slender limbs [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…A number of small Arthroleptis species have been described from the mountains and the graben valley of the Albertine Rift [3,8,[13][14][15][16], and three species of Arthroleptis have been recorded from Rwanda [17]. Arthroleptis adolfifriederici Nieden, 1911 was described from the "Bugoiewald" and the "Rugegewald" (nowadays Gishwati and Nyungwe Forest, respectively) in Rwanda and is easily identified by its large size, smooth dorsum and long and slender limbs [13,17]. Arthroleptis schubotzi Nieden, 1911 has its type locality at "Usumbura" (=Bujumbura, Burundi) and was later also recorded from southwestern Tanzania, eastern Democratic Republic of the Congo, and western Rwanda [8,13,15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations